Arthur's teacher trouble - Brown, Marc Tolon (Boston : Little Brown, 1986)
Third-grader Arthur is amazed when he is chosen to be in the school spellathon.
Book Links (A.L.A.).
Elem. School Library Collection.
School Library Journal.
2.4
3.8.
K-3
Keywords: Animals -- Fiction; Arthur (Fictitious character : Brown) -- Fiction; English language -- Spelling -- Fiction; Schools -- Fiction; Teachers -- Fiction; Animals -- Fiction; Arthur (Fictional character : Brown) -- Fiction; School stories; Spelling -- Fiction; Teachers -- Fiction